Septin6 regulates cell growth and casein synthesis in dairy cow mammary epithelial cells via mTORC1 pathway. Issue 2 (24th May 2019) - Li, Bin; Basang, Zhuzha; Hu, Lijun; Liu, Liu; Jiang, Nan
Abstract: This research paper addresses the hypothesis that Septin6 is a key regulatory factor influencing amino acid (AA)-mediated cell growth and casein synthesis in dairy cow mammary epithelial cells (DCMECs). DCMECs were treated with absence of AA (AA−), restricted concentrations of AA (AAr) or normal concentrations of AA (AA+) for 24 h. Cell growth, expression of CSN2 and Septin6 were increased in response to AA supply. Overexpressing or inhibiting Septin6 demonstrated that cell growth, expression of CSN2, mTOR, p-mTOR, S6K1 and p-S6K1 were up-regulated by Septin6. Furthermore, overexpressing or inhibiting mTOR demonstrated that the increase in cell growth and expression of CSN2 in response to Septin6 overexpression were inhibited by mTOR inhibition, and vice versa. Our hypothesis was supported; we were able to show that Septin6 is an important positive factor for cell growth and casein synthesis, it up-regulates AA-mediated cell growth and casein synthesis through activating mTORC1 pathway in DCMECs.